2015
DOI: 10.3233/jad-150394
|View full text |Cite
|
Sign up to set email alerts
|

N-Truncated Aβ2-X Starting with Position Two in Sporadic Alzheimer’s Disease Cases and Two Alzheimer Mouse Models

Abstract: According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Furthermore, elongated amyloidogenic Aβ 1–43 peptides have recently been reported [ 6 ]. Similar heterogeneity has been observed at the Aβ N-terminus, and several N-terminally truncated Aβ forms, including Aβ 2–x [ 7 ], Aβ pE3–x [ 8 , 9 ], Aβ 5–x [ 10 , 11 ], and Aβ pE11–x [ 9 , 12 , 13 ], have been demonstrated in parenchymal or vascular deposits of human AD brains by immunohistochemical methods. An even more complex pattern of Aβ peptides has been reported by the use of mass spectrometry [ 14 17 ], which detected further variants such as Aβ 7–42 , Aβ 8–42 , or Aβ 9–42 .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, elongated amyloidogenic Aβ 1–43 peptides have recently been reported [ 6 ]. Similar heterogeneity has been observed at the Aβ N-terminus, and several N-terminally truncated Aβ forms, including Aβ 2–x [ 7 ], Aβ pE3–x [ 8 , 9 ], Aβ 5–x [ 10 , 11 ], and Aβ pE11–x [ 9 , 12 , 13 ], have been demonstrated in parenchymal or vascular deposits of human AD brains by immunohistochemical methods. An even more complex pattern of Aβ peptides has been reported by the use of mass spectrometry [ 14 17 ], which detected further variants such as Aβ 7–42 , Aβ 8–42 , or Aβ 9–42 .…”
Section: Introductionsupporting
confidence: 60%
“…For SDS-PAGE analysis, stock solutions of synthetic Aβ 1–40 , Aβ 2–40 , Aβ 3–40 , pyroglutamate Aβ 3–40 (Aβ pE3–40 ), and Aβ 4–40 were prepared in sample buffer (0.36 M bis-tris, 0.16 M bicine, 15% wt/vol sucrose, 1% wt/vol SDS, and 0.0075% wt/vol bromophenol blue) and stored at −80 °C. The Aβ peptides were further diluted in sample buffer, and aliquots containing 0.1, 1, and 10 ng of peptide per lane were separated by urea-bicine/bis-tris/Tris/sulfate SDS-PAGE and analyzed by immunoblotting as previously described [ 7 ]. The blotting membranes were blocked in 2% electrochemiluminescence (ECL) advance blocking agent (GE Healthcare Life Sciences, Little Chalfont, UK) in PBS with 0.1% Tween 20 (PBS-T) for at least 4 h at room temperature (RT) and probed with the primary antibody 029-2 (1:300 in PBS-T) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…an Aβ 2-x -specific polyclonal antibody confirmed the presence of Aβ 2-x peptides in both parenchymal and vascular deposits of sporadic AD cases as well as transgenic mouse models such as APP/PS1KI or 5XFAD (37). As the sequence of fulllength Aβ starts with an Asp residue in position 1, it has been suggested that proteolysis of Aβ 1-x peptides by the exopeptidase aminopeptidase A, which releases Glu and Asp residues from the N-termini of proteins, could result in the generation of Aβ 2-x species (38).…”
Section: Aβ 2-xmentioning
confidence: 73%
“…One-dimensional urea-Bicine/Bis-Tris/Tris/sulfate SDS-PAGE (1D-Aβ-PAGE) was carried out as described previously [ 45 ]. Protein extracts were prepared from 12-month-old WT and 5XFAD mouse brain hemispheres by sequential extraction with Tris-buffered saline (TBS, 120 mM NaCl, 50 mM Tris, pH7.5) and 2 % sodium dodecyl sulfate (SDS).…”
Section: Methodsmentioning
confidence: 99%
“…Following centrifugation for 20 min at 17000 x g, the resulting pellet was sonified in 2 % SDS and centrifuged for 20 min at 17000 x g. The protein concentrations of the supernatants were determined with the Roti-Quant protein assay (Carl Roth). Aβ peptide immunoprecipitation was carried out with mAb6E10 (Covance) as previously described [ 18 , 45 ]. For Western-immunoblot analysis, samples with a protein concentration of 2 mg/mL were prepared in electrophoresis sample buffer (final composition: 0.36 M Bistris, 0.16 M bicine, 15 % (w/v) sucrose, 1 % (w/v) SDS, 0,0075 % bromophenol blue).…”
Section: Methodsmentioning
confidence: 99%